2017
DOI: 10.1194/jlr.m073049
|View full text |Cite
|
Sign up to set email alerts
|

DOCK2 deficiency mitigates HFD-induced obesity by reducing adipose tissue inflammation and increasing energy expenditure

Abstract: Obesity is the major risk factor for type 2 diabetes, cardiovascular disorders, and many other diseases. Adipose tissue inflammation is frequently associated with obesity and contributes to the morbidity and mortality. Dedicator of cytokinesis 2 (DOCK2) is involved in several inflammatory diseases, but its role in obesity remains unknown. To explore the function of DOCK2 in obesity and insulin resistance, WT and DOCK2-deficient (DOCK2) mice were given chow or high-fat diet (HFD) for 12 weeks followed by metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…Dedicator of cytokinesis 2 (DOCK2) is involved in several inflammatory diseases. A recent experimental study indicated that DOCK2 deficiency might protect mice from high-fat-diet induced obesity by reducing adipose tissue inflammation and increasing energy expenditure (Guo et al, 2017 ). Our findings on the role of DOCK6 and DGKB in BMI-WHR were supported by two meta-analyses respectively which identified genome-wide significant signals near DOCK6 for total cholesterol in Hispanics (Below et al, 2016 ) and near DGKB for beta cell function in East Asians (Hong et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dedicator of cytokinesis 2 (DOCK2) is involved in several inflammatory diseases. A recent experimental study indicated that DOCK2 deficiency might protect mice from high-fat-diet induced obesity by reducing adipose tissue inflammation and increasing energy expenditure (Guo et al, 2017 ). Our findings on the role of DOCK6 and DGKB in BMI-WHR were supported by two meta-analyses respectively which identified genome-wide significant signals near DOCK6 for total cholesterol in Hispanics (Below et al, 2016 ) and near DGKB for beta cell function in East Asians (Hong et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when fed a diet with high saturated fatty acids, DOCK5 expression was found to be elevated in vivo compared with baseline levels, in conjunction with the accumulation of fat. In addition, among members of the DOCK-A subfamily, DOCK2 has been found to be associated with metabolic homeostasis, obesity, and IR [12]. In addition, among members of the DOCK-A subfamily, DOCK2 has been found to be associated with metabolic homeostasis, obesity, and IR [12].…”
Section: Introductionmentioning
confidence: 99%
“…SIT1 [93], JAML (junction adhesion molecule like) [94], TIMP1 [95], PRKCB (protein kinase C beta) [96], MMP7 [97], WNT7B [98], WNT10A [99], DUSP1 [100], WT1 [101], APOC3 [102], ERRFI1 [103], HCN2 [104], MME (membrane metalloendopeptidase) [105], STRA6 [106], SLC12A3 [107] and GC (GC vitamin D binding protein) [108] expedites epithelial to mesenchymal transition and renal brosis in DN. Previous studies have found CFD (complement factor D) [109], DOCK2 [110], LYZ (lysozyme) [111], CD5L [112], SCARA5 [113], VCAN (versican) [114], GDF5 [115], SFRP2 [116], BTG2 [117], ZFP36 [118], GPR3 [119], OLR1 [120], PM20D1 [121] and UGT2B7 [122] to be expressed in obesity, but these genes might be liable for advancement of DN. Polymorphic FCRL3 [123], FCGR2B [124], COMP (cartilage oligomeric matrix protein) [125], ERFE (erythroferrone) [126] and NPHS1 [127] expression can be altered by in ammation, which might involved in nephropathy.…”
Section: Discussionmentioning
confidence: 99%